2015
DOI: 10.5430/jnep.v6n4p65
|View full text |Cite
|
Sign up to set email alerts
|

Elevated distress among patients undergoing screening for lung cancer

Abstract: Objective: Low-dose CT scanning has recently been recommended to screen patients at elevated risk of developing lung cancer, however, limited data exist describing distress experienced by this at-risk population. The objective of this study is to describe the prevalence and risk factors of high distress among patients undergoing screening for lung cancer. Methods: The validated National Comprehensive Cancer Network Distress Thermometer (DT) was used to evaluate distress prior to and following lung cancer scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“… 35 Among a total of 228 patients with lung cancer, the percentage of distress was 58.2% vs 33.6% in women and men, respectively. 36 Among 5335 patients with cancer assessed by DT screenings, the prevalence of distress was 36.0% vs 28.7% in women and men, respectively. 37 A recent review indicated that the prevalence of distress in pan-cancer patients was higher in female compared with male.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 35 Among a total of 228 patients with lung cancer, the percentage of distress was 58.2% vs 33.6% in women and men, respectively. 36 Among 5335 patients with cancer assessed by DT screenings, the prevalence of distress was 36.0% vs 28.7% in women and men, respectively. 37 A recent review indicated that the prevalence of distress in pan-cancer patients was higher in female compared with male.…”
Section: Discussionmentioning
confidence: 98%
“…Using HADS evaluation, there was 41% distress in female patients with lung cancer compared with a 29% in male patients, which is a remarkable difference 35. Among a total of 228 patients with lung cancer, the percentage of distress was 58.2% vs 33.6% in women and men, respectively 36. Among 5335 patients with cancer assessed by DT screenings, the prevalence of distress was 36.0% vs 28.7% in women and men, respectively 37.…”
Section: Discussionmentioning
confidence: 98%
“…Although the effects of an interaction between family cancer history and own cancer diagnosis on mental health and distress are well established in the context of cancers of lung or breast [10, 11], the effects of such interaction on physical functioning or physical symptoms were not thoroughly investigated. Researchers indicated that individuals who perceive themselves as at higher risk for cancer due to family cancer history experience a significant increment of distress [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers indicated that individuals who perceive themselves as at higher risk for cancer due to family cancer history experience a significant increment of distress [10, 11]. Elevated distress levels, in turn, explain poorer physical QOL among cancer patients [12, 13].…”
Section: Introductionmentioning
confidence: 99%